Single dose IV ketamine for adolescent suicidal ideation in the emergency department: a pilot randomized trial - Schlegelmilch, Michael; Plint, Amy C.; Barrowman, Nicholas; Gray, Clare; Crawford, Tyrus; Kutcher, Stephen A.; Bhatt, Maala (Université d'Ottawa | University of Ottawa, 2026)
Abstract Background Suicidal ideation (SI) is a common reason for emergency department (ED) visits by adolescents. While intravenous (IV) ketamine rapidly reduces SI in adults, its efficacy in adolescents remains unstudied. We assessed the feasibility of a trial of a single dose IV ketamine to reduce adolescent SI in the ED. Methods This double-blind, randomized, placebo-controlled pilot trial was conducted from Jan-May 2024. Medically stable adolescents aged 12 to 17 years with moderate-to-severe SI were eligible. Participants were randomized to IV ketamine (0.5 mg/kg; max 50 mg) or IV normal saline (0.5 ml/kg; max 50 mL), infused over 40 min. They were monitored for 120 min and then received usual ED mental health care. The primary outcome was trial feasibility (enrolment and follow-up success). The primary clinical outcome was SI severity at 40 min post-infusion (T-40), measured using the Beck Scale for SI (SSI5), Montgomery-Asberg Depression Rating Scale item 10 (MADRS10) and Beck Depression Inventory item 9 (BDI9). Additional outcomes included hospital admission, adverse events, 30-day ED revisits and death. Results Twenty participants were eligible and were enrolled. All participants completed the infusion and day-1 follow-up; 90% completed day-7 follow-up. No serious adverse events occurred. While SI severity did not differ significantly between groups at T-40 (SSI5: p = 0.06; MADRS10: p = 0.19; BDI9: p = 0.18), fewer participants randomized to ketamine were hospitalized at the initial visit (risk difference 40%, 95%CI: 7, 69%). Conclusions Recruiting adolescents to an ED-based IV ketamine study for SI is feasible. A larger trial is needed to clarify potential clinical benefits. Trial registration ClinicalTrials.gov ID NCT06366334 (Registered 20240412).